Discounting health: The issue of subsistence and care in an undeveloped country - Messing, Simon D (Social Science & Medicine, 1973)
The concept "discounting health" is proposed as a heuristic model for analysis of differing perceptions concerning "cost-benefit", as these relate to systems of health care. This procedure became necessary during analysis of data gathered in rural Ethiopia to measure the effectiveness of new Health Centers. Ethnological research accompanying the quantitative study of health attitudes found that "subsistence anxiety" dominated all other concerns of the majority in the rural areas. The landless peasant sharecropper and his divorced wife represent the most prevalent social problem in Ethiopia. Holistic solutions should include some form of social security and safe wells, so that the population can stop "discounting health". © 1973.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-649-364-861-026 tex.type: [object Object]
Keywords: Absenteeism; Anxiety; Attitude to Health; Child; Community Health Services; Delivery of Health Care; Economics; Epidemiology; Ethiopia; Ethnic Groups; Health Education; Human; Income; Legislation; Medical; Life Style; Models; Theoretical; Preventive Health Services; Questionnaires; Rural Health; Sanitation; anxiety; dept.ant; developing country; finance; health center; health service; methodology; model; primary health care; public health service